The Impact Of Brand Image On Online Purchase Decisions Of Sociolla Marketplace Users In Surabaya - Maulidiyah, Nailin Nikmatul (Nomico, 2024)
Technological and economic developments in the current era have led many companies in Indonesia to further maximize the function and role of marketing in entering the era of globalization. The internet doesn't have to be accessed via a computer anymore, but simply by using a smartphone. The purpose of this research is to analyze the impact of brand image on online purchase decisions. Online shopping is an activity of purchasing goods or services carried out via the internet, or online buying and selling services without having to bring buyers and sellers together directly. The trend towards purchasing branded beauty products is growing rapidly due to the high level of public enthusiasm for purchasing these products. The type of this research is a quantitative research using simple linear regression analysis. The population in this research are all Sociolla marketplace users. The sampling method used in this research is purposive random sampling as many as 50 people. The results of this research show that consumer brand image has a positive and significant effect on online purchase decisions